NS’ role in defining the vision of a new society - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2017)
Yesterday marked the 50th anniversary of the introduction of National Service (NS), a cornerstone of our defence strategy and a hallmark of the Singaporean way of life. In a short span of 50 years, NS has come a long way and continues to mould generations of Singaporean men.